EVALUASI FUNGSI REGULASI DINAS KESEHATAN PROVINSI PADA SEKTOR KESEHATAN DI PROVINSI BENGKULU - , ADLIN FITRI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Government Act Number 38 issued in 2007 on the differentiation of government affairs between central government, local provincial and local district/municipal government stated the obligation of local district/municipal government to protect, serve, empower and ensure welfare of the community as well as implement regulation in health sector. Based on data of Bengkulu Provincial Health Office, some health facilities and staff do not register, take accreditation and certification. This indicates that regulation function is not yet well implemented. Thus it is necessary to evaluate function of provincial health office in the implementation of regulation in health sector. Objective: To evaluate regulation function of Bengkulu Provincial Health Office as regulator in health sector, viewed from input, process, output and environment. Method: The study was qualitative with case study design. Evaluation of function of Bengkulu Provincial Health Office was made on regulation in health sector, i.e. licensing, registration, accreditation and sertification of health facilities and staff against standard in the implementation of regulation on licensing, registration and certification. Result: Performance in input for the implementation of regulation was still relatively weak: there was no support of regulation or policy in the implementation of regulation, there was no staff specifically responsible for the implementation of regulation, no budget allocation for regulation function implementation, no standard or method for the implementation of control and supervision, and facilities for the operation of regulation were limited. This caused poor performance of regulation implementation so that the output was poor, some health facilities and staff were no registered, there was no accreditation and certification. There was no role of the environment, i.e. office of integrated registration service that regulated licensing. Conclusion: Regulation function of Bengkulu Provincial Health Office in health sector was not well implemented due to lack of support from the government as viewed from input, process, output and environment in the implementation of regulation function in licensing, registration, accreditation and certification.